Morphological Indicators Of The Lymphoid Structures Of The Spleen Of White Rats In Postnatal Ontogenesis In The Dynamics Of Age - Ziyoda Rakhmonovna, Sokhibova; Mashrab Rustamovich, Turdiyev; Dilnoza Fazliddinovna, Ibodova; Ravshanovna, Toirova Dilafro’z (Journal of Neonatal Surgery, 2025)
The article studies the structural parameters of the spleen of white rats in postnatal ontogenesis in the dynamics of age. It was found that in postnatal ontogenesis, morphological and morphometric parameters of the white pulp of the spleen of white rats undergo significant changes, which is reflected in different age aspects. In newborn white rats, the spleen is functionally immature. At three and six months of age, the spleen has the maximum potential for immunogenesis. At the age of twelve months, the processes of age-related organ involution begin, which are expressed by changes in the structure of the white pulp of the spleen